STUDENTS’ MOTIVATION IN ONLINE LEARNING DURING COVID-19 PANDEMIC ERA: A CASE STUDY - Sri Gustiani (HOLISTICS, 2020)
The purpose of this study is to illuminate the motivation of the students at English Department of Sriwijaya Polytechnics toward their online learning during the Covid-19 pandemic era. Due to sudden transformation from traditional face-to-face learning approach to remotely digital learning, some present studies revealed that students’ motivation in online learning was affected both intrinsically and extrinsically. Using snowball sampling, there were eight students participated in individual interviews and fourteen students in focus group interviews. The gained data from both interviews were analysed using thematic analysis. It was revealed that the students’ motivation toward their online learning was intrinsically affected more by their ambition to learn new knowledge and enjoyment in experiencing new learning method. It was also influenced extrinsically by external regulation and environmental condition. However, amotivation or the state of lack motivation also happened due to poor external supporting facilities.